Diseño de una estrategia de aprendizaje significativo basada en un videojuego educativo sobre deberes escolares (2020)
Design of a meaningful learning strategy based on an educational video game about school duties: The research deals with the negative incidence of the non-fulfillment of the school duties of the students of the grade 8-5 of the I. E., Sagrada Familia Palmira, in the academic performance and in the construction of civic competences in coexistence. The significant learning strategy included simulated situations from the educational gamification with the use of an educational video game and activities in values such as responsibility, self-control, respect for authority and norms, to reflect on school duties. Theoretical references were the construction in citizenship and the ways of living well by John Dewey; the involvement of homework in Regueiro education and Ausubel meaningful learning. With the strategy, the students expanded their cognitive structure and made better theoretical anchors on these values; they advanced in school duties related to coexistence and respect for teachers. The results obtained showed achievements regarding the design of a video game and some complementary activities that captured the interest and enthusiasm of the students and that made it possible for them to reflect on how to act in their social, political and citizen dimension, so that they understand what is necessary to interrelate with others, to achieve healthy coexistence and the ways of living well. However, this reflection did not mean that they transformed their habits and behaviors of non-compliance and inappropriate behaviors into their daily lives at school. The research approach; is qualitative, based on the action participation research approach; the method used is a case study. Keywords: Educational video games, meaningful learning, citizenship competencies, construction in citizenship, school duties.